Competitive anxiety and performance in competing sailors (Ansiedad competitiva y rendimiento en deportistas de vela) - Salom Martorell, Miquel; Ponseti, Francisco Xavier; Contestí Bosch, Bernat; Salom Ferragut, Gaspar; García-Mas, Alexandre; Núñez Prats, Antonio (Retos (Madrid), 2021)
In this study we analyze the connection between competitive anxiety (its cognitive and somatic factors) and performance in sailing sport. It has been typically accepted that anxiety is detrimental to sports performance. However, it is currently being intensively investigated whether the anxiety levels are always harmful to sports performance, as the data yielded by recent studies are contradictory. A data collection was carried out, involving 69 federated sailors from the Balearic Islands (Spain) with a mean age of 26.38 years ranging from 10 to 64 years. In order to analyze the psychological variables, athletes were given the adapted Spanish version of the Sports Anxiety Scale (SAS-2) and the performance of the sailors was evaluated. The results show that no differences are found in the anxiety levels between the high and low performance groups. Resumen. En este estudio analizamos la relación entre la ansiedad competitiva (en sus componentes cognitivos y somáticos) y el rendimiento en el deporte de la vela. Clásicamente se ha aceptado que la ansiedad es perjudicial para el rendimiento deportivo. Actualmente se investiga intensamente sobre si los niveles de ansiedad son siempre perjudiciales para el rendimiento deportivo, debido a que los datos hallados en recientes estudios son contradictorios. Para ello, se realizó una recogida de datos, donde participaron 69 deportistas federados en vela de las Islas Baleares con una edad media de 26.38 años y un rango de entre 10 y 64 años. Para analizar las variables psicológicas a los deportistas se les administró la versión española adaptada de la Escala de Ansiedad en el Deporte (SAS-2) y se evaluó el rendimiento de los regatistas. Los resultados muestran que no se encuentran diferencias en los niveles de ansiedad entre los grupos de alto y bajo rendimiento.